2006
DOI: 10.1242/jcs.02740
|View full text |Cite
|
Sign up to set email alerts
|

Suppressors of cytokine signaling (SOCS) 1 and SOCS3 interact with and modulate fibroblast growth factor receptor signaling

Abstract: interaction between FGFR3 and SOCS1 on receptor activity was investigated in a chondrocytic cell line overexpressing SOCS1. In these cells, STAT1 phosphorylation is repressed, MAPK phosphorylation is elevated and prolonged, and FGFR3 downregulation is attenuated. Expression of osteopontin (OPN), which is directly upregulated by FGF in chondrocytes, was stimulated by lower levels of FGF in cells expressing SOCS1 compared with parental cells. Blocking of MAPK phosphorylation by PD98059 decreased OPN expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 68 publications
3
43
0
Order By: Relevance
“…Furthermore, SOCS-3 can bind to tyrosine kinase receptors and interfere with their signal transduction. Ben-Zvi et al (2006) could show that SOCS-3 and SOCS-1 bind to FGFR3 in HEK-293T cells. In those cells, SOCS-1 overexpression elevated MAPK phosphorylation, in contrast to the effect of SOCS-3 in prostate cancer, and repressed STAT1 phosphorylation.…”
Section: Socs-3 Is a Regulator Of Receptor Tyrosine Kinasesmentioning
confidence: 96%
“…Furthermore, SOCS-3 can bind to tyrosine kinase receptors and interfere with their signal transduction. Ben-Zvi et al (2006) could show that SOCS-3 and SOCS-1 bind to FGFR3 in HEK-293T cells. In those cells, SOCS-1 overexpression elevated MAPK phosphorylation, in contrast to the effect of SOCS-3 in prostate cancer, and repressed STAT1 phosphorylation.…”
Section: Socs-3 Is a Regulator Of Receptor Tyrosine Kinasesmentioning
confidence: 96%
“…Similar to INSR, EGFR induces tyrosine phosphorylation of SOCS3 [58]. Another RTK, FGFR3 was found to be constitutively associated with SOCS3 independent of FGF stimulation or the receptor's kinase activity [36,57]. Thus it is most likely that SOCS3 associates with the RTKs and regulates downstream signaling by ubiquitination-dependent degradation of receptor.…”
Section: Socs3mentioning
confidence: 98%
“…Thus, it is suggested that SOCS1 association with FGFR3 and EGFR has similar regulatory functions as other RTKs. On the other hand, SOCS1 cooperated with FGFR3 to promote FGF induced MAPK phosphorylation through a still undefined mechanism [36]. A possible explanation is that SOCS proteins may not only act as ubiquitin ligases but also as adapters.…”
Section: Socs1mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, SOCS1is involved in the regulation of several receptors including platelet-derived growth factor receptor (PDGFR), colony-stimulating factor 1 receptor (CSF1R), FMS-like tyrosine kinase 3 (FLT3), stem cell factor (SCF) receptor (KIT), insulin receptor (INSR), proto-oncogene MET and AXL [8][9][10][11][12][13][14]. Similar regulatory roles were described for SOCS2, SOCS3 and SOCS6 as well [1].…”
Section: Socs Family Proteinsmentioning
confidence: 99%